An Analytical Study in The Arabic-English Translation of Al-Tin Surah - Salah, Aula AbdulGhaffour Muhammad (Journal of Humanities & Social Sciences, 2022)
The religious translation is one of the important types of translation. The translation of it is not easy. It has a number of difficulties that the translator may face during translation. This leads him/her to use a number of strategies that enable him/ her to translate the religious texts efficiently. This research comprises three sections. Section one presents definitions of translation. Section two deals with the analytical levels of translation (lexical, syntactic, semantic, phonological and stylistic levels). Section three investigates such levels in the translation of Surah Al-Tin l and analyse their implications in translation. Finally, the conclusions have been drawn.